(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Choroshilowa N. V. Forms of Foreign Languages Teaching in the Adults’ Education System in Germany. The article deals with the specific features of alternative forms of teaching foreign languages in Germany such as intensive teaching, distance teaching, media communication teaching. Selected issues of the organization and methodical support, especially intensive and distance learning of foreign languages, specificity of adult learning in the foreign languages training. are studied.